ANALISIS KINERJA PERALATAN MONOPULSE SECONDARY SURVEILLANCE RADAR MODE-S MEREK INDRA TYPE IRS20-MP/S 2NA TERHADAP KESELAMATAN PENERBANGAN - Numan Ahlur Rayi Qaiz; Dian Anggraini Purwaningtyas; Adenia Kusuma Dayanthi (STEKOM PRESS, 2024)
Monopulse Secondary Surveillance Radar Mode-S is a flight observation device that can work up to 256 NM coverage. To ensure that the equipment is run, it is necessary to evaluate the performance of the equipment in accordance with KP No. 35 of 2019 concerning procedures for maintenance and reporting of aviation telecommunications facilities. The purpose of this study is to evaluate the performance of the tool. Equipment performance evaluation is analyzed based on several parameters. the analysis was carried out using research methods in the form of qualitative analysis and descriptive analysis. The results of the analysis are adjusted to KP no. 35 of 2019 with an evaluation of the performance of the INDRA IRS20-MP/S 2NA Type MSSR Mode-S Radar device for the 2023 period has 100% availability, MTBF 8760 Hours, and MTTR 0 Minutes